INTERNALISASI NILAI-NILAI MODERASI BERAGAMA MELALUI PEMBELAJARAN PAI DI SEKOLAH MULTIKULTURAL: STUDI KASUS DI SMA NEGERI 17 TEBO - Yanti, Ely; Sabli, Muhammad; Kurniawan, Sugeng; Andryadi; Yulia Friska, Sonia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2023)
Identity polarization and potential intolerance at the secondary school level demand the strengthening of religious moderation internalization as a foundation for national character. This study aimed to map the internalization process of religious moderation values through Islamic Religious Education (PAI) in a multicultural school context. A qualitative case study design was implemented at SMA Negeri 17 Tebo Regency involving four PAI teachers, 15 students from diverse cultural/religious backgrounds, one principal, and one community leader. Data were collected through in-depth interviews, participatory observation (4 months, 24 meetings), and policy/RPP document analysis. Thematic analysis revealed three internalization dimensions: cognitive (contextual understanding of religious texts & religious literacy), affective (empathy, teacher modeling, interfaith dialogue), and behavioral (cross-identity collaboration, peaceful conflict resolution, social participation). Findings indicate that internalization effectiveness depends on teachers’ pedagogical strategies integrating moral exemplarity, multicultural case-based learning, and explicit-hidden curriculum synergy. Key challenges include limited affective-behavioral assessment tools, parental resistance to interfaith dialogue, and insufficient teacher training in moderation-oriented instructional design. This study recommends developing structured internalization assessment rubrics, PAI modules contextualized to Tebo, and teacher training oriented toward contact pedagogy. The contribution lies in mapping the micro-process of religious moderation internalization in PAI and providing an operational framework adoptable by similar multicultural schools.